MATHEMATICAL MODELS OF ELECTROMAGNETIC EFFECTS OF THE TRACTION SYSTEM ON THE ADJACENT LINES - Amirov Sulton; Otabek Boltayev; Firuza Akhmedova; Bakhrom Nurxonov (European Journal of Humanities and Educational Advancements, 2023)
In the article, mathematical models of the electric and magnetic effects of the traction system under tension on the approach lines are developed, taking into account the reverse effect of the approach line. Also, the current and voltage values generated in the adjacent line in different modes of the adjacent line were analyzed and it was determined that the most dangerous voltage generated in the adjacent line due to the electric effect of the affected line is generated in the first mode, and the most dangerous voltage generated due to the magnetic effect is generated in the second mode.